Adhesive film for circuit connection, circuit connection structure and method for manufacturing the same
By using a circuit connection adhesive film with a minimum melt viscosity of 450 to 1600 Pa·s in COP package, the circuit breakage problem caused by deformation of the plastic substrate during hot pressing is solved, and good conduction characteristics between the opposite electrodes are achieved.
Patent Information
- Application Number
- CN202180045457.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-07
- Filing Date
- 2021-07-05
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-07-05
AI Technical Summary
In COP packaging, the thermal and mechanical properties of the plastic substrate are different from those of the COG packaging, which leads to deformation of the plastic substrate during hot pressing, which may lead to circuit breakage.
An adhesive film for circuit connection is adopted, which consists of a first adhesive layer and a second adhesive layer. The first adhesive layer contains conductive particles, a cured product of a photocurable resin component and a first thermosetting resin component. The second adhesive layer contains a second thermosetting resin component and has a minimum melt viscosity of 450 to 1600 Pa·s.
This adhesive film can effectively prevent circuit wiring from being broken during hot crimping, and ensure good conduction characteristics between opposite electrodes of the circuit connection structure.
Smart Images

Figure CN115777008B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive film for circuit connection, a circuit connection structure and a manufacturing method thereof. Background Art
[0002] In the past, liquid crystal display panels, organic EL panels, etc. have been used as various display mechanisms such as televisions, PC monitors, mobile phones, and smartphones. In such display devices, from the perspectives of fine pitch, light weight, and thinness, so-called COG (chip on glass) packaging is adopted in which a driver IC is packaged directly on a glass substrate of a display panel.
[0003] In a liquid crystal display panel that adopts the COG packaging method, for example, a semiconductor element such as a liquid crystal driver IC is connected to a transparent substrate (glass substrate, etc.) having a plurality of transparent electrodes (ITO (indium tin oxide) etc.). As an adhesive material for connecting the electrode terminals of the semiconductor element and the transparent electrodes, a circuit connection adhesive film having anisotropic conductivity in which conductive particles are dispersed in the adhesive is used. For example, in the case of packaging a liquid crystal driver IC as a semiconductor element, a plurality of electrode terminals corresponding to the transparent electrodes are provided on the packaging surface of the liquid crystal driver IC, and the liquid crystal driver IC is thermally pressed onto the transparent substrate via a circuit connection adhesive film having anisotropic conductivity, thereby connecting the electrode terminals to the transparent electrodes, and thus a circuit connection structure can be obtained.
[0004] In recent years, a display having a curved surface (flexible display) has been proposed. In such a flexible display, a flexible plastic substrate (polyimide substrate, etc.) is used as a substrate instead of a glass substrate, thereby also encapsulating various electronic components such as a driver IC on the plastic substrate. As such an encapsulation method, COP (chip on plastic) encapsulation using an adhesive film for circuit connection having anisotropic conductivity has been studied (for example, refer to Patent Document 1).
[0005] Previous technical literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-054288 Summary of the invention
[0008] Technical issues to be solved by the invention
[0009] In the case of COP packaging, the thermal and mechanical properties of the substrate are different from those of COG packaging. During thermocompression bonding, the plastic substrate deforms in a bulging manner, which accumulates stress in the circuit and sometimes causes circuit disconnection. In addition, a pressure-sensitive adhesive layer such as a pressure-sensitive resin and a film such as PET (polyethylene terephthalate) and PEN (polyethylene naphthalate) are usually arranged on the lower surface of the plastic substrate. During thermocompression bonding, the pressure-sensitive resin flows, which tends to further promote the deformation of the plastic substrate.
[0010] A main object of the present invention is to provide an adhesive film for circuit connection that can prevent circuit disconnection during thermocompression bonding and ensure good conduction characteristics between electrodes facing each other in a circuit connection structure.
[0011] Means for solving technical problems
[0012] One aspect of the present invention relates to an adhesive film for circuit connection. The adhesive film for circuit connection comprises: a first adhesive layer containing conductive particles, a cured product of a photocurable resin component, and a first thermosetting resin component; and a second adhesive layer disposed on the first adhesive layer and containing a second thermosetting resin component. The minimum melt viscosity of the adhesive film for circuit connection is 450 to 1600 Pa·s. According to this adhesive film for circuit connection, the conductive particles during circuit connection can be effectively captured by curing the photocurable resin component. Furthermore, if the minimum melt viscosity of the adhesive film for circuit connection is 450 Pa·s or more, deformation of the plastic substrate during thermocompression bonding can be suppressed and circuit disconnection can be prevented. Furthermore, if the minimum melt viscosity of the adhesive film for circuit connection is 1600 Pa·s or less, the decrease in resin expellability during circuit connection can be suppressed, thereby reducing the connection resistance between the opposing electrodes of the circuit connection structure, thereby ensuring good conduction characteristics. Such an adhesive film for circuit connection can be applied to COP packaging, and more specifically, can be applied to connection between a plastic substrate having circuit electrodes formed thereon and an IC chip such as a driver IC in an organic EL display.
[0013] The first thermosetting resin component and the second thermosetting resin component may contain a cationic polymerizable compound and a thermal cationic polymerization initiator, and the photocurable resin component may contain a free radical polymerizable compound. At this time, the first thermosetting resin component and the second thermosetting resin component have cationic curability, and the photocurable resin component has free radical curability. According to the research of the present inventors, if the first thermosetting resin component and the second thermosetting resin component and the photocurable resin component are such a combination, then, for example, compared with the case where all curable resin components have cationic curability, the connection resistance tends to be more excellent. As a reason for exerting such an effect, the inventors of the present invention speculate as follows. That is, it is believed that the reason is that if all curable resin components have cationic curable components, for example, in the first adhesive layer, when forming a cured product of the photocurable resin component, cationic active species may sometimes remain, and the curing reaction of the second thermosetting resin component in the second adhesive layer is carried out by the cationic active species, resulting in a decrease in the expulsion of the resin. Therefore, if the photocurable resin component has radical curability, no cationic active species are generated when the photocurable resin component is cured, so that the curing reaction of the second thermosetting resin component in the second adhesive layer can be suppressed, and the connection resistance can be further reduced.
[0014] The cationically polymerizable compound may be at least one selected from the group consisting of oxetane compounds and alicyclic epoxy compounds. The thermal cationic polymerization initiator may be a salt compound having an anion containing boron as a constituent element.
[0015] The thickness of the first adhesive layer may be 5 μm or less. When the thickness of the first adhesive layer is 5 μm or less, the conductive particles can be more effectively captured during circuit connection.
[0016] Another aspect of the present invention relates to a method for manufacturing a circuit connection structure. The method for manufacturing a circuit connection structure includes the following steps: interposing the circuit connection adhesive film between a first circuit component having a first electrode and a second circuit component having a second electrode, and performing thermal compression bonding on the first circuit component and the second circuit component to electrically connect the first electrode and the second electrode to each other.
[0017] Another aspect of the present invention relates to a circuit connection structure. The circuit connection structure comprises: a first circuit component having a first electrode; a second circuit component having a second electrode; and a circuit connection portion disposed between the first circuit component and the second circuit component to electrically connect the first electrode and the second electrode to each other. The circuit connection portion comprises a cured product of the circuit connection adhesive film.
[0018] Effects of the Invention
[0019] According to the present invention, a circuit connection adhesive film is disclosed, which can prevent the occurrence of circuit disconnection during thermal compression bonding and can ensure good conduction characteristics between the opposing electrodes of the circuit connection structure. This circuit connection adhesive film can be applied to COP packaging. In addition, according to the present invention, a circuit connection structure using this circuit connection adhesive film and a manufacturing method thereof are disclosed. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic cross-sectional view showing one embodiment of the adhesive film for circuit connection.
[0021] Figure 2 It is a schematic cross-sectional view showing one embodiment of a circuit connection structure.
[0022] Figure 3 This is a schematic cross-sectional view showing one embodiment of a method for manufacturing a circuit-connected structure. Figure 3 (a) and Figure 3 (b) is a schematic cross-sectional view showing each step. DETAILED DESCRIPTION
[0023] Hereinafter, the embodiments of the present invention will be described in detail with reference to the accompanying drawings. In the following description, the same or corresponding parts are marked with the same symbols, and repeated descriptions are omitted. In addition, the present invention is not limited to the following embodiments.
[0024] In this specification, the numerical range indicated by "~" indicates a range including the numerical values recorded before and after "~" as the minimum value and the maximum value, respectively. In the numerical range recorded in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can be replaced by the upper limit or lower limit of the numerical range of other stages. And, in the numerical range recorded in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment. And, the upper limit and lower limit recorded separately can be combined arbitrarily. In the mark of the numerical range "A~B", the numerical values A and B at both ends are included in the numerical range as the lower limit and the upper limit, respectively. In this specification, for example, the record of "more than 10" refers to "10" and "a numerical value exceeding 10", and this shall prevail in the case of different numerical values. And, for example, the record of "less than 10" refers to "10" and "a numerical value less than 10", and this shall prevail in the case of different numerical values. And, in this specification, "(meth)acrylate" refers to at least one of acrylate and its corresponding methacrylate. The same also applies to other similar expressions such as "(meth)acryloyl" and "(meth)acrylic acid". Furthermore, "A or B" may include either A or B, or both. Furthermore, unless otherwise specified, the materials exemplified below may be used alone or in combination of two or more. When there are multiple substances equivalent to each component in the composition, the content of each component in the composition refers to the total amount of the multiple substances present in the composition, unless otherwise specified.
[0025] [Adhesive film for circuit connection]
[0026] Figure 1 This is a schematic cross-sectional view showing one embodiment of the adhesive film for circuit connection. Figure 1 The circuit connection adhesive film 10 shown in the figure (hereinafter, sometimes simply referred to as "adhesive film 10") comprises: a first adhesive layer 1 containing conductive particles 4, and an adhesive component 5 containing a cured product of a photocurable resin component and a (first) thermosetting resin component; and a second adhesive layer 2 disposed on the first adhesive layer 1 and containing a (second) thermosetting resin component. In the adhesive film 10, there may be a first region formed by the first adhesive film (first adhesive layer 1) and a second region disposed adjacent to the first region and formed by the second adhesive film (second adhesive layer 2). That is, the adhesive film 10 may also comprise: a first region containing conductive particles 4, and an adhesive component 5 containing a cured product of a photocurable resin component and a (first) thermosetting resin component; and a second region disposed adjacent to the first region and containing a (second) thermosetting resin component.
[0027] In the adhesive film 10, the conductive particles 4 are dispersed in the first adhesive layer 1. Therefore, the adhesive film 10 can be an adhesive film for circuit connection having anisotropic conductivity (anisotropic conductive adhesive film). The adhesive film 10 can be interposed between a first circuit component having a first electrode and a second circuit component having a second electrode, and is used to perform thermal compression bonding on the first circuit component and the second circuit component to electrically connect the first electrode and the second electrode to each other.
[0028] <First adhesive layer>
[0029] The first adhesive layer 1 contains conductive particles 4 (hereinafter, sometimes referred to as "(A) component"), a cured product of a photocurable resin component (hereinafter, sometimes referred to as "(B) component"), and a thermosetting resin component (hereinafter, sometimes referred to as "(C) component"). The first adhesive layer 1 can be obtained, for example, by irradiating a composition layer containing the (A) component, the (B) component, and the (C) component with light energy, polymerizing the components contained in the (B) component, and curing the (B) component. The first adhesive layer 1 contains the (A) component, and an adhesive component 5 containing a cured product of the (B) component and the (C) component. The cured product of the (B) component can be a cured product obtained by completely curing the (B) component, or a cured product obtained by curing a portion of the (B) component. The (C) component is a component that can flow when the circuit is connected, for example, an uncured curable resin component.
[0030] (A) Ingredients: Conductive particles
[0031] Regarding component (A), there is no particular limitation as long as it is a particle with conductivity, and it can be a metal particle composed of a metal such as Au, Ag, Pd, Ni, Cu, solder, etc., a conductive carbon particle composed of conductive carbon, etc. Component (A) can be a coated conductive particle having a core (including non-conductive glass, ceramics, plastic (polystyrene, etc.)) and a coating layer (including the above-mentioned metal or conductive carbon and coating the core). Among them, component (A) is preferably a coated conductive particle having a core (including metal particles or plastics formed by hot-melt metal) and a coating layer (including metal or conductive carbon and coating the core). Such coated conductive particles can easily deform the cured product of the thermosetting resin component by heating or pressurizing, so when the electrodes are electrically connected to each other, the contact area between the electrode and component (A) can be increased, and the conductivity between the electrodes can be further improved.
[0032] The (A) component may be an insulating coated conductive particle having the above-mentioned metal particles, conductive carbon particles or coated conductive particles and an insulating layer containing an insulating material such as a resin and coating the surface of the particle. If the (A) component is an insulating coated conductive particle, even if the content of the (A) component is high, since the surface of the particle is provided with an insulating layer, the occurrence of a short circuit caused by contact between the (A) components can be suppressed, and the insulation between adjacent electrode circuits can also be improved. The (A) component may be used alone or in combination of two or more of the above-mentioned various conductive particles.
[0033] The maximum particle size of the (A) component needs to be smaller than the minimum spacing between the electrodes (the shortest distance between adjacent electrodes). From the perspective of excellent dispersibility and conductivity, the maximum particle size of the (A) component can be greater than 1.0 μm, greater than 2.0 μm, or greater than 2.5 μm. From the perspective of excellent dispersibility and conductivity, the maximum particle size of the (A) component can be less than 20 μm, less than 10 μm, or less than 5 μm. In this specification, for any 300 (pcs) conductive particles, the particle size is measured by observation using a scanning electron microscope (SEM), and the maximum value obtained is used as the maximum particle size of the (A) component. In addition, in the case where the (A) component has protrusions, the (A) component is not spherical, and the particle size of the (A) component is the diameter of the circle circumscribed with the conductive particles in the SEM image.
[0034] From the viewpoint of excellent dispersibility and conductivity, the average particle size of component (A) may be 1.0 μm or more, 2.0 μm or more, or 2.5 μm or more. From the viewpoint of excellent dispersibility and conductivity, the average particle size of component (A) may be 20 μm or less, 10 μm or less, or 5 μm or less. In this specification, for any 300 (pcs) conductive particles, the particle size is measured by observation using a scanning electron microscope (SEM), and the average value of the obtained particle size is taken as the average particle size.
[0035] In the first adhesive layer 1, the component (A) is preferably uniformly dispersed. From the viewpoint of obtaining a stable connection resistance, the particle density of the component (A) in the adhesive film 10 may be 100 particles / mm 2 Above, 1000 pieces / mm 2 Above, 3000 pieces / mm 2 Above or 5000 pcs / mm 2 From the viewpoint of improving the insulation between adjacent electrodes, the particle density of the component (A) in the adhesive film 10 may be 100,000 particles / mm 2 Below, 70,000 pieces / mm 2 Below, 50000 pieces / mm 2Below or 30000 pcs / mm 2 the following.
[0036] From the viewpoint of further improving the conductivity, based on the total mass of the first adhesive layer,
[0037] The content of component (A) may be 1% by mass or more, 5% by mass or more, or 10% by mass or more. From the perspective of easily suppressing short circuits, the content of component (A) may be 60% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total mass of the first adhesive layer. If the content of component (A) is within the above range, the effect of the present invention tends to be significantly exerted. In addition, the content of component (A) in the composition or composition layer (total mass basis of the composition or composition layer) may be the same as the above range.
[0038] (B) Component: Photocurable resin component
[0039] There are no particular restrictions on the component (B) as long as it is a resin component that is cured by light irradiation. However, when the component (C) is a resin component having cation curability, the component (B) may be a resin component having free radical curability from the viewpoint of having better connection resistance. The component (B) may include, for example, a free radical polymerizable compound (hereinafter, sometimes referred to as "component (B1)") and a photo radical polymerization initiator (hereinafter, sometimes referred to as "component (B2)"). The component (B) may be a component consisting of the component (B1) and the component (B2).
[0040] Component (B1): Radical polymerizable compound
[0041] The component (B1) is a compound that is polymerized by free radicals generated by the component (B2) by irradiation with light (e.g., ultraviolet light). The component (B1) may be any one of a monomer or a polymer (or oligomer) obtained by polymerization of one or more monomers. The components (B1) may be used alone or in combination of multiple types.
[0042] (B1) component is a compound having a radical polymerizable group that reacts by free radicals. As the radical polymerizable group, for example, (meth) acryloyl, vinyl, allyl, styryl, alkenyl, alkenylene, maleimide, etc. can be cited. From the viewpoint that after polymerization, the desired melt viscosity is easily obtained, the effect of reducing the connection resistance is further improved, and the connection reliability is more excellent, the number of radical polymerizable groups (functional group number) possessed by the (B1) component can be more than 2, and from the viewpoint of suppressing the curing shrinkage during polymerization, it can be less than 10. In addition, in order to maintain the balance between the crosslinking density and the curing shrinkage, in addition to the compounds whose number of radical polymerizable groups is within the above range, compounds whose number of radical polymerizable groups is outside the above range can also be used.
[0043] From the viewpoint of suppressing the flow of the conductive particles, for example, the component (B1) may contain a polyfunctional (two or more functional) (meth)acrylate. The polyfunctional (two or more functional) (meth)acrylate may be a bifunctional (meth)acrylate, and the bifunctional (meth)acrylate may be a bifunctional aromatic (meth)acrylate.
[0044] Examples of the polyfunctional (meth)acrylate include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethoxylated polypropylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, Acid ester, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, glycerol di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, ethoxylated 2-methyl-1,3-propanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, ethoxylated propoxylated trimethylolpropane tri(meth)acrylate Aliphatic (meth)acrylates such as hydroxymethylpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tri(meth)acrylate, propoxylated pentaerythritol tri(meth)acrylate, ethoxylated propoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethoxylated propoxylated pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc.; ethoxylated bisphenol A di(meth)acrylate, propoxylated Aromatic (meth)acrylates such as ethoxylated bisphenol A di(meth)acrylate, ethoxylated propoxylated bisphenol A di(meth)acrylate, ethoxylated bisphenol F di(meth)acrylate, propoxylated bisphenol F di(meth)acrylate, ethoxylated propoxylated bisphenol F di(meth)acrylate, ethoxylated fluorene di(meth)acrylate, propoxylated fluorene di(meth)acrylate, ethoxylated propoxylated fluorene di(meth)acrylate; aromatic epoxy (meth)acrylates such as bisphenol epoxy (meth)acrylate, novolac epoxy (meth)acrylate, cresol novolac epoxy (meth)acrylate, etc.
[0045] From the viewpoint of achieving both the effect of reducing connection resistance and suppressing particle flow, the content of the polyfunctional (bifunctional or higher) (meth)acrylate may be, for example, 40 to 100 mass %, 50 to 100 mass %, or 60 to 100 mass % based on the total mass of the component (B1).
[0046] Component (B1) may contain a monofunctional (meth)acrylate in addition to a multifunctional (two or more functional) (meth)acrylate. Examples of the monofunctional (meth)acrylate include (meth)acrylic acid; methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, butoxyethyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octylheptyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate , 2-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolypropylene glycol (meth)acrylate, mono(2-(meth)acryloyloxyethyl)succinate and other aliphatic (meth)acrylates; benzyl (meth)acrylate, phenyl (meth)acrylate, o-biphenyl (meth)acrylate, 1(meth)acrylate -naphthyl (meth)acrylate, 2-naphthyl (meth)acrylate, phenoxyethyl (meth)acrylate, p-cumylphenoxyethyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, 1-naphthyloxyethyl (meth)acrylate, 2-naphthyloxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate, phenoxypolypropylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxy-3-(o-phenylphenoxy)propyl Aromatic (meth)acrylates such as propyl (meth)acrylate, 2-hydroxy-3-(1-naphthyloxy)propyl (meth)acrylate, and 2-hydroxy-3-(2-naphthyloxy)propyl (meth)acrylate; (meth)acrylates having an epoxy group such as glycidyl (meth)acrylate, (meth)acrylates having an alicyclic epoxy group such as 3,4-epoxycyclohexyl methyl (meth)acrylate, and (meth)acrylates having an oxetane group such as (3-ethyloxetan-3-yl)methyl (meth)acrylate.
[0047] The content of the monofunctional (meth)acrylate may be, for example, 0 to 60% by mass, 0 to 50% by mass, or 0 to 40% by mass based on the total mass of the component (B1).
[0048] The cured product of the component (B) may, for example, have a polymerizable group that reacts other than free radicals. The polymerizable group that reacts other than free radicals may, for example, be a cationic polymerizable group that reacts by cations. As cationic polymerizable groups, for example, epoxy groups such as glycidyl, alicyclic epoxy groups such as epoxycyclohexylmethyl, oxetane groups such as ethyloxetanemethyl, etc. may be cited. The cured product of the component (B) having a polymerizable group that reacts other than free radicals can be introduced as the component (B) by using, for example, (meth)acrylates having epoxy groups, (meth)acrylates having alicyclic epoxy groups, (meth)acrylates having oxetane groups, etc., which have polymerizable groups that react other than free radicals. From the viewpoint of improving reliability, the mass ratio of the (meth)acrylate having a polymerizable group that reacts other than by free radicals to the total mass of the component (B1) (mass (charged amount) of the (meth)acrylate having a polymerizable group that reacts other than by free radicals / total mass (charged amount) of the component (B1)) can be, for example, 0 to 0.7, 0 to 0.5 or 0 to 0.3.
[0049] In addition to multifunctional (two or more functional) and monofunctional (meth) acrylates, component (B1) may also include other free radical polymerizable compounds. As other free radical polymerizable compounds, for example, maleimide compounds, vinyl ether compounds, allyl compounds, styrene derivatives, acrylamide derivatives, nadic imide derivatives, etc. can be cited. Based on the total mass of component (B1), the content of other free radical polymerizable compounds can be, for example, 0 to 40% by mass.
[0050] Component (B2): Photoradical polymerization initiator
[0051] The component (B2) is a photopolymerization initiator that generates free radicals by irradiating light having a wavelength in the range of 150 to 750 nm, preferably light having a wavelength in the range of 254 to 405 nm, and more preferably light having a wavelength of 365 nm (for example, ultraviolet light). The components (B2) may be used alone or in combination of two or more.
[0052] The (B2) component is decomposed by light and generates free radicals. That is, the (B2) component is a compound that generates free radicals by applying light energy from the outside. The (B2) component can be a compound having structures such as an oxime ester structure, a bisimidazole structure, an acridine structure, an α-aminoalkylphenone structure, an aminobenzophenone structure, an N-phenylglycine structure, an acylphosphine oxide structure, a benzyldimethylketal structure, and an α-hydroxyalkylphenone structure. The (B2) component can be used alone or in combination. From the viewpoint of easily obtaining the desired melt viscosity and the viewpoint of having a better effect of reducing the connection resistance, the (B2) component can be a compound having at least one structure selected from the group consisting of an oxime ester structure, an α-aminoalkylphenone structure, and an acylphosphine oxide structure.
[0053] Specific examples of the compound having an oxime ester structure include 1-phenyl-1,2-butanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-o-benzoyloxime, 1,3-diphenylpropanetrione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-3-ethoxypropanetrione-2-(o-benzoyl)oxime, 1,2-octanedione, 1-[4-(phenylthio)phenyl-, 2-(o-benzoyloxime)], ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(o-acetyloxime), and the like.
[0054] Specific examples of the compound having an α-aminoalkylphenone structure include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one and 2-benzyl-2-dimethylamino-1-morpholinophenyl)-butanone-1-one.
[0055] Specific examples of the compound having an acylphosphine oxide structure include bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, bis(2,4,6,-trimethylbenzoyl)-phenylphosphine oxide, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0056] From the viewpoint of suppressing the flow of the conductive particles, the content of the component (B2) may be, for example, 0.1 to 10 parts by mass, 0.3 to 7 parts by mass, or 0.5 to 5 parts by mass based on 100 parts by mass of the component (B1).
[0057] From the viewpoint of suppressing the flow of conductive particles, the content of the cured product of the (B) component may be 1% by mass or more, 5% by mass or more, or 10% by mass or more, based on the total mass of the first adhesive layer. From the viewpoint of showing low resistance in low-voltage packaging, the content of the cured product of the (B) component may be 50% by mass or less, 40% by mass or less, or 30% by mass or less, based on the total mass of the first adhesive layer. If the content of the cured product of the (B) component is within the above range, the effect of the present invention tends to be significantly exerted. In addition, the content of the (B) component in the composition or composition layer (the total mass basis of the composition or composition layer) may be the same as the above range.
[0058] (C) Component: Thermosetting resin component
[0059] There is no particular limitation on the (C) component as long as it is a resin component that is cured by light irradiation. However, when the (B) component is a resin component having free radical curability, from the perspective of having better connection resistance, the (C) component may be a resin component having cation curability. The (C) component may, for example, contain a cationic polymerizable compound (hereinafter, sometimes referred to as "component (C1)") and a thermal cationic polymerization initiator (hereinafter, sometimes referred to as "component (C2)"). The (C) component may be a component composed of components (C1) and (C2). In addition, the first thermosetting resin component and the second thermosetting resin component refer to thermosetting resin components contained in the first adhesive layer and the second adhesive layer, respectively. The types, combinations and contents of the components contained in the first thermosetting resin component and the second thermosetting resin component (for example, component (C1), component (C2), etc.) may be the same as or different from each other.
[0060] Component (C1): Cationic polymerizable compound
[0061] (C1) component is a compound that reacts with (C2) component by heat and crosslinks. In addition, (C1) component refers to a compound that does not have a free radical polymerizable group that reacts by free radicals, and (C1) component is not included in (B1) component. From the viewpoint of further improving the effect of reducing the connection resistance and better connection reliability, (C1) component can be, for example, at least one selected from the group consisting of oxetane compounds and alicyclic epoxy compounds. (C1) component can be used alone or in combination. From the viewpoint of easily obtaining the desired melt viscosity, (C1) component preferably includes at least one oxetane compound and at least one alicyclic epoxy compound.
[0062] As the oxetane compound of (C1) component, as long as it is a compound having an oxetane group and not having a free radical polymerizable group, it can be used without particular limitation. As a commercially available product of the oxetane compound, for example, ETERNACOLL OXBP (trade name, manufactured by UBE Corporation), OXSQ, OXT-121, OXT-221, OXT-101, OXT-212 (trade name, manufactured by TOAGOSEI CO., LTD.) etc. can be cited. These can be used alone as one compound, or a plurality of compounds can be used in combination.
[0063] As the alicyclic epoxy compound of component (C1), as long as it is a compound having an alicyclic epoxy group (e.g., epoxycyclohexyl) and not having a radical polymerizable group, it can be used without particular limitation. As commercially available products of alicyclic epoxy compounds, for example, EHPE3150, EHPE3150CE, CEL8010, CEL2021P, CEL2081 (trade name, manufactured by Daicel Corporation) and the like can be cited. These can be used alone or in combination of multiple compounds.
[0064] Component (C2): thermal cationic polymerization initiator
[0065] The component (C2) is a thermal polymerization initiator that generates an acid or the like by heating to initiate polymerization. The component (C2) may be a salt compound composed of a cation and an anion. For example, the component (C2) may include a compound having BF 4 - , BR 4 - (R represents a phenyl group substituted with two or more fluorine atoms or two or more trifluoromethyl groups.) PF 6 - , SbF 6 - , AsF 6 - Onium salts such as sulfonium salts, phosphonium salts, ammonium salts, diazonium salts, iodonium salts, and aniline salts of anions, etc. These may be used alone or in combination of two or more.
[0066] From the viewpoint of storage stability, the component (C2) may have an anion containing boron as a constituent element, that is, BF 4 - or BR 4 - (R represents a phenyl group substituted with two or more fluorine atoms or two or more trifluoromethyl groups.) The anion containing boron as a constituent element may be BR 4 -, more specifically, tetrakis(pentafluorophenyl)borate.
[0067] Since the onium salt as the component (C2) has resistance to substances that may inhibit the curing relative to the cationic curing, for example, an aniline salt may be used. Examples of the aniline salt compound include N,N-dimethylaniline salt, N,N-diethylaniline salt and other N,N-dialkylaniline salts.
[0068] The component (C2) may be an aniline salt having an anion containing boron as a constituent element. Examples of commercially available products of such salt compounds include CXC-1821 (trade name, manufactured by King Industries, Inc.).
[0069] From the viewpoint of ensuring the formability and curability of the adhesive film for forming the first adhesive layer, the content of the component (C2) can be, for example, 0.1 to 25 parts by mass, 1 to 20 parts by mass, 3 to 18 parts by mass, or 5 to 15 parts by mass relative to 100 parts by mass of the component (C1).
[0070] From the viewpoint of ensuring the curability of the adhesive film for forming the first adhesive layer, the content of the (C) component can be 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more, based on the total mass of the first adhesive layer. From the viewpoint of ensuring the formatibility of the adhesive film for forming the first adhesive layer, the content of the (C) component can be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total mass of the first adhesive layer. If the content of the (C) component is within the above range, the effect of the present invention tends to be significantly exerted. In addition, the content of the (C) component in the composition or composition layer (the total mass basis of the composition or composition layer) can be the same as the above range.
[0071] Other Ingredients
[0072] The first adhesive layer 1 may contain other components in addition to the cured product of the component (A), the component (B) and the component (C). Other components include, for example, a thermoplastic resin (hereinafter, sometimes referred to as the "component (D)"), a coupling agent (hereinafter, sometimes referred to as the "component (E)"), a filler (hereinafter, sometimes referred to as the "component (F)"), etc.
[0073] As component (D), for example, phenoxy resin, polyester resin, polyamide resin, polyurethane resin, polyester polyurethane resin, acrylic rubber, epoxy resin (solid at 25°C), etc. can be cited. These can be used alone or in combination. By containing the composition of component (A), component (B) and component (C) and also containing component (D), a composition layer (and then the first adhesive layer 1) can be easily formed from the composition. Among these, component (D) can be, for example, a phenoxy resin.
[0074] From the viewpoint of resin expulsion during encapsulation, the weight average molecular weight (Mw) of the component (D) may be, for example, 5,000 to 200,000, 10,000 to 100,000, 20,000 to 80,000, or 40,000 to 60,000. Mw refers to a value measured by gel permeation chromatography (GPC) and converted using a calibration curve based on standard polystyrene.
[0075] Based on the total mass of the first adhesive layer, the content of the component (D) may be 1% by mass or more, 5% by mass or more, 10% by mass or more, or 20% by mass or less, or 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less. In addition, the content of the component (D) in the composition or the composition layer (based on the total mass of the composition or the composition layer) may be the same as the above range.
[0076] As (E) component, for example, silane coupling agents having organic functional groups such as (meth) acryloyl, mercapto, amino, imidazole, epoxy, etc., silane compounds such as tetraalkoxysilane, tetraalkoxy titanate derivatives, polydialkyl titanate derivatives, etc. can be cited. These can be used alone or in combination. By containing (E) component in the first adhesive layer 1, the adhesion can be further improved. (E) component can be, for example, a silane coupling agent. Based on the total mass of the first adhesive layer, the content of (E) component can be 0.1 to 10% by mass. In addition, the content of (E) component in the composition or composition layer (total mass basis of the composition or composition layer) can be the same as the above range.
[0077] As the (F) component, for example, non-conductive fillers (for example, non-conductive particles) can be mentioned. The (F) component can be any of an inorganic filler and an organic filler. As an inorganic filler, for example, metal oxide particles such as silica particles, alumina particles, silica-alumina particles, titanium dioxide particles, zirconium dioxide particles; inorganic particles such as metal nitride particles can be mentioned. As an organic filler, for example, organic particles such as silicone particles, methacrylate / butadiene / styrene particles, acrylic / silicone particles, polyamide particles, and polyimide particles can be mentioned. These can be used alone or in combination. The (F) component can be, for example, silica particles. Based on the total mass of the first adhesive layer, the content of the (F) component can be 0.1 to 10% by mass. In addition, the content of the (F) component in the composition or the composition layer (based on the total mass of the composition or the composition layer) can be the same as the above range.
[0078] Other additives
[0079] The first adhesive layer 1 may also contain other additives such as a softener, an accelerator, an anti-degradation agent, a colorant, a flame retardant, a thixotropic agent, etc. Based on the total mass of the first adhesive layer, the content of other additives may be, for example, 0.1 to 10% by mass. In addition, the content of other additives in the composition or composition layer (based on the total mass of the composition or composition layer) may be the same as the above range.
[0080] The thickness d1 of the first adhesive layer 1 may be, for example, 5 μm or less. The thickness d1 of the first adhesive layer 1 may be 4.5 μm or less or 4.0 μm or less. The thickness d1 of the first adhesive layer 1 is 5 μm or less, thereby being able to further effectively capture the conductive particles during circuit connection. The thickness d1 of the first adhesive layer 1 may be, for example, 0.1 μm or more, 0.5 μm or more, or 0.7 μm or more. In addition, the thickness d1 of the first adhesive layer 1 may be obtained by, for example, sandwiching an adhesive film between two glasses (thickness: about 1 mm), injecting a resin composition composed of 100 g of bisphenol A epoxy resin (trade name: JER811, manufactured by Mitsubishi Chemical Corporation) and 10 g of a curing agent (trade name: Epomount curing agent, manufactured by Refine Tec Ltd.), performing cross-section grinding using a grinder, and measuring using a scanning electron microscope (SEM, trade name: SE-8020, manufactured by Hitachi High-Tech Science Corporation). And, if Figure 1As shown in FIG. 1 , when a portion of the conductive particles 4 are exposed from the surface of the first adhesive layer 1 (for example, protruding toward the second adhesive layer 2 side), the distance (in the range of 0 to 100°) from the surface 2a of the first adhesive layer 1 on the side opposite to the second adhesive layer 2 side to the boundary S between the first adhesive layer 1 and the second adhesive layer 2 located at the separation portion between the adjacent conductive particles 4 and 4 is Figure 1 The distance d1 in FIG. 1 is the thickness of the first adhesive layer 1, and the exposed portion of the conductive particles 4 is not included in the thickness of the first adhesive layer 1. The length of the exposed portion of the conductive particles 4 may be, for example, 0.1 μm or more, or 5 μm or less.
[0081] <Second adhesive layer>
[0082] The second adhesive layer 2 contains component (C). Component (C1) and component (C2) used in component (C) (i.e., second thermosetting resin component) in the second adhesive layer 2 are the same as component (C1) and component (C2) used in component (C) (i.e., first thermosetting resin component) in the first adhesive layer 1, and thus detailed description thereof is omitted here. The second thermosetting resin component may be the same as or different from the first thermosetting resin component.
[0083] From the viewpoint of maintaining reliability, the content of the component (C) may be 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more based on the total mass of the second adhesive layer. From the viewpoint of preventing resin seepage on the reel as one form of supply, the content of the component (C) may be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 45% by mass or less based on the total mass of the second adhesive layer.
[0084] The second adhesive layer 2 may further contain other components and other additives in the first adhesive layer 1. Preferred aspects of the other components and other additives are the same as those of the first adhesive layer 1.
[0085] The content of the component (D) may be 1 mass % or more, 5 mass % or more, or 10 mass % or less, or 80 mass % or less, 60 mass % or less, or 40 mass % or less based on the total mass of the second adhesive layer.
[0086] The content of the component (E) may be 0.1 to 10% by mass based on the total mass of the second adhesive layer.
[0087] The content of the component (F) may be 1 mass % or more, 5 mass % or more, or 10 mass % or less, or 70 mass % or less, 50 mass % or less, or 30 mass % or less based on the total mass of the second adhesive layer.
[0088] The content of other additives may be, for example, 0.1 to 10% by mass based on the total mass of the second adhesive layer.
[0089] The thickness d2 of the second adhesive layer 2 can be appropriately set according to the height of the electrodes of the bonded circuit components, etc. From the viewpoint of being able to fully fill the space between the electrodes to seal the electrodes and to obtain better connection reliability, the thickness d2 of the second adhesive layer 2 can be greater than 5 μm or greater than 7 μm, or less than 15 μm or less than 11 μm. In addition, the thickness d2 of the second adhesive layer 2 can be obtained, for example, by the same method as the measurement method of the thickness d1 of the first adhesive layer 1. Furthermore, in a case where a portion of the conductive particles 4 are exposed from the surface of the first adhesive layer 1 (for example, protruding toward the second adhesive layer 2 side), the distance (at the boundary S between the first adhesive layer 1 and the second adhesive layer 2 at the separation portion of the adjacent conductive particles 4, 4) from the surface 3a of the second adhesive layer 2 on the opposite side to the first adhesive layer 1 side is Figure 1 The distance represented by d2 in the figure is the thickness of the second adhesive layer 2.
[0090] The thickness of the adhesive film 10 (the total thickness of all layers constituting the adhesive film 10, in Figure 1 In the embodiment, the total thickness (the total thickness d1 of the first adhesive layer 1 and the thickness d2 of the second adhesive layer 2) may be, for example, 5 μm or more or 8 μm or more, or 30 μm or less or 20 μm or less.
[0091] The minimum melt viscosity of the adhesive film 10 is 450 to 1600 Pa·s. The minimum melt viscosity of the adhesive film 10 may be 500 Pa·s or more, 600 Pa·s or more, 700 Pa·s or more, or 800 Pa·s or more. If the minimum melt viscosity of the adhesive film 10 is 450 Pa·s or more, deformation of the plastic substrate during thermal compression bonding can be suppressed and circuit disconnection can be prevented. The minimum melt viscosity of the adhesive film 10 may be 1500 Pa·s or less, 1400 Pa·s or less, 1300 Pa·s or less, 1200 Pa·s or less, 1100 Pa·s or less, or 1000 Pa·s or less. If the minimum melt viscosity of the adhesive film 10 is 1600 Pa·s or less, the reduction in the expulsion of the resin during circuit connection can be suppressed, thereby reducing the connection resistance between the opposing electrodes of the circuit connection structure and ensuring good conduction characteristics. The minimum melt viscosity of the adhesive film can be determined, for example, by the method described in Examples.
[0092] In the adhesive film 10, the second adhesive layer 2 is usually thicker than the first adhesive layer 1. Therefore, the minimum melt viscosity of the adhesive film 10 tends to vary according to the second adhesive layer 2. The minimum melt viscosity of the adhesive film 10 can be adjusted, for example, by adjusting the type and content of the constituent components (particularly, the (D) component) contained in the second adhesive layer 2. In addition, the minimum melt viscosity of the adhesive film 10 can also be adjusted, for example, by using a component with a small particle size as the (F) component. By using a component with a small particle size as the (F) component, the minimum melt viscosity of the adhesive film 10 tends to increase.
[0093] In the adhesive film 10, the conductive particles 4 are dispersed in the first adhesive layer 1. Therefore, the adhesive film 10 is an anisotropic conductive adhesive film having anisotropic conductivity. The adhesive film 10 is interposed between the first circuit component having the first electrode and the second circuit component having the second electrode, and is used to perform thermal compression bonding on the first circuit component and the second circuit component to electrically connect the first electrode and the second electrode to each other.
[0094] According to the adhesive film 10, the conductive particles during circuit connection can be effectively captured by curing the photocurable resin component. Furthermore, if the minimum melt viscosity of the adhesive film 10 is 450 Pa·s or more, the deformation of the plastic substrate during thermocompression bonding can be suppressed and the occurrence of circuit disconnection can be prevented. Furthermore, if the minimum melt viscosity of the adhesive film 10 is 1600 Pa·s or less, the decrease in the resin removability during circuit connection can be suppressed, thereby reducing the connection resistance between the opposing electrodes of the circuit connection structure and ensuring good conduction characteristics. Therefore, the occurrence of circuit disconnection during thermocompression bonding can be prevented and good conduction characteristics between the opposing electrodes of the circuit connection structure can be ensured. This adhesive film 10 can be suitable for COP packaging, and more specifically, can be suitable for connecting a plastic substrate having circuit electrodes formed thereon in an organic EL display and an IC chip such as a driver IC.
[0095] As mentioned above, although the adhesive film of this embodiment was demonstrated, this invention is not limited to the said embodiment.
[0096] The adhesive film may be composed of two layers, the first adhesive layer and the second adhesive layer, or may be composed of three or more layers including the first adhesive layer and the second adhesive layer. The adhesive film may also include a third adhesive layer, which is disposed on the side of the first adhesive layer opposite to the second adhesive layer and contains a (third) thermosetting resin component. In the adhesive film, there may be a first region formed by the first adhesive film (first adhesive layer) and a third region disposed adjacent to the first region and formed by the third adhesive film (third adhesive layer). The adhesive film may also include a third region disposed adjacent to the first region on the side opposite to the second region and containing a (third) thermosetting resin component.
[0097] The third adhesive layer contains component (C). Component (C1) and component (C2) used in component (C) (i.e., the third thermosetting resin component) in the third adhesive layer are the same as component (C1) and component (C2) used in component (C) (i.e., the first thermosetting resin component) in the first adhesive layer 1, and thus detailed description thereof is omitted here. The third thermosetting resin component may be the same as or different from the first thermosetting resin component. The third thermosetting resin component may be the same as or different from the second thermosetting resin component.
[0098] From the viewpoint of imparting good transferability and peeling resistance, the content of the component (C) may be 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more, based on the total mass of the third adhesive layer. From the viewpoint of imparting good half-cutting properties and blocking resistance (suppressing resin exudation on the reel), the content of the component (C) may be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total mass of the third adhesive layer.
[0099] The third adhesive layer may further contain other components and other additives in the first adhesive layer 1. Preferred aspects of the other components and other additives are the same as those of the first adhesive layer 1.
[0100] The content of the component (D) may be 10 mass % or more, 20 mass % or more, or 30 mass % or less, or 80 mass % or less, 70 mass % or less, or 60 mass % or less based on the total mass of the third adhesive layer.
[0101] The content of the component (E) may be 0.1 to 10% by mass based on the total mass of the third adhesive layer.
[0102] The content of the component (F) may be 1 mass % or more, 3 mass % or more, or 50 mass % or less, 40 mass % or less, or 30 mass % or less based on the total mass of the third adhesive layer.
[0103] The content of other additives may be, for example, 0.1 to 10% by mass based on the total mass of the third adhesive layer.
[0104] The thickness of the third adhesive layer can be appropriately set according to the minimum melt viscosity of the adhesive film, the height of the electrode of the bonded circuit component, etc. The thickness of the third adhesive layer is preferably smaller than the thickness d2 of the second adhesive layer 2. From the perspective of being able to fully fill the space between the electrodes and seal the electrodes, and obtaining better connection reliability, the thickness of the third adhesive layer can be greater than 0.2 μm, or less than 3.0 μm. In addition, the thickness of the third adhesive layer can be obtained, for example, by the same method as the measurement method of the thickness d1 of the first adhesive layer 1.
[0105] Furthermore, the circuit-connecting adhesive film of the above-described embodiment is an anisotropic conductive adhesive film having anisotropic conductivity, but the circuit-connecting adhesive film may be a conductive adhesive film not having anisotropic conductivity.
[0106] [Method for producing adhesive film for circuit connection]
[0107] The manufacturing method of the circuit connection adhesive film of one embodiment may include, for example, a step of irradiating a composition layer made of a composition containing component (A), component (B) and component (C) (first thermosetting resin component) with light to form a first adhesive layer (first step); and a step of laminating a second adhesive layer containing component (C) (second thermosetting resin component) on the first adhesive layer (second step). The manufacturing method may also include the following step (third step): laminating a third adhesive layer containing component (C) (third thermosetting resin component) on the layer on the side opposite to the second adhesive layer of the first adhesive layer.
[0108] In the first step, for example, first, a composition containing component (A), component (B) and component (C), as well as other components and other additives added as needed, is stirred, mixed, kneaded, etc. in an organic solvent, thereby dissolving or dispersing it, thereby preparing a varnish composition. Thereafter, a blade coater, a roller coater, an applicator, a notched wheel coater, a die coater, etc. are used to apply the varnish composition to a substrate subjected to a demolding treatment, and then the organic solvent is volatilized by heating to form a composition layer on the substrate. At this time, by adjusting the coating amount of the varnish composition, the thickness of the first adhesive layer (first adhesive film) finally obtained can be adjusted. Next, the composition layer is irradiated with light to cure the component (B) in the composition layer, and the first adhesive layer is formed on the substrate. The first adhesive layer can be referred to as the first adhesive film.
[0109] Regarding the organic solvent used in the preparation of the varnish composition, as long as it has the characteristic of being able to uniformly dissolve or disperse each component, there is no particular restriction. As such an organic solvent, for example, toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, butyl acetate, etc. can be cited. These organic solvents can be used alone or in combination with more than two kinds. The stirring and mixing or mixing during the preparation of the varnish composition can be carried out, for example, using a stirrer, a mortar machine, a three-roller, a ball mill, a bead mill, a homogenizing dispersion machine, etc.
[0110] Regarding the substrate, as long as it has heat resistance that can withstand the heating conditions when the organic solvent is volatilized, there is no particular restriction. As this substrate, for example, a substrate (for example, a film) made of stretched polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene / vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber system, liquid crystal polymer, etc. can be used.
[0111] The heating conditions for volatilizing the organic solvent from the varnish composition applied on the substrate can be appropriately set according to the organic solvent used, etc. The heating conditions may be, for example, 40 to 120° C. and 0.1 to 10 minutes.
[0112] In the light irradiation in the curing process, it is preferred to use irradiation light having a wavelength in the range of 150 to 750 nm (e.g., ultraviolet light). Regarding the light irradiation, for example, a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a metal halide lamp, an LED light source, etc. can be used. The cumulative light amount of the light irradiation can be appropriately set, but for example, it can be 500 to 3000 mJ / cm 2 .
[0113] The second step is a step of laminating the second adhesive layer on the first adhesive layer. In the second step, for example, first, the second adhesive layer is formed on the substrate in the same manner as the first step, using component (C), other components and other additives added as needed, and no light irradiation is performed, to obtain a second adhesive film. Then, the second adhesive layer can be laminated on the first adhesive layer by laminating the first adhesive film and the second adhesive film. In addition, in the second step, for example, a varnish composition obtained by using component (C) and other components and other additives added as needed is applied on the first adhesive layer, and the organic solvent is volatilized, thereby laminating the second adhesive layer on the first adhesive layer.
[0114] Examples of the method for laminating the first adhesive film and the second adhesive film include heat pressing, roll lamination, vacuum lamination, etc. The lamination can be performed at a temperature of 0 to 80°C, for example.
[0115] The third step is a step of laminating a third adhesive layer on the layer on the side opposite to the second adhesive layer of the first adhesive layer. In the third step, for example, first, in the same manner as in the second step, a third adhesive layer is formed on a substrate to obtain a third adhesive film. Next, the third adhesive film is laminated on the side opposite to the second adhesive film of the first adhesive film, thereby laminating the third adhesive layer on the layer on the side opposite to the second adhesive layer of the first adhesive layer. Furthermore, in the third step, for example, in the same manner as in the second step, a varnish composition is applied on the layer on the side opposite to the second adhesive layer of the first adhesive layer, and the organic solvent is volatilized, thereby laminating the second adhesive layer on the first adhesive layer. The laminating method and conditions are the same as those in the second step.
[0116] [Circuit connection structure and method for manufacturing the same]
[0117] Hereinafter, a circuit connection structure using the above-mentioned circuit connection adhesive film 10 as a circuit connection material and a method for producing the same will be described.
[0118] Figure 2 Schematic cross-sectional view showing one embodiment of a circuit connection structure. Figure 2 As shown, the circuit connection structure 20 comprises: a first circuit component 13, having a first electrode 12 formed on a first circuit substrate 11 and a main surface 11a of the first circuit substrate 11; a second circuit component 16, having a second electrode 15 formed on a second circuit substrate 14 and a main surface 14a of the second circuit substrate 14; and a circuit connection portion 17, arranged between the first circuit component 13 and the second circuit component 16, electrically connecting the first electrode 12 and the second electrode 15 to each other.
[0119] The first circuit component 13 and the second circuit component 16 may be the same or different from each other. The first circuit component 13 and the second circuit component 16 may be a glass substrate or a plastic substrate on which circuit electrodes are formed; a printed circuit board; a ceramic circuit board; a flexible circuit board; an IC chip such as a driver IC, etc. The first circuit substrate 11 and the second circuit substrate 14 may be formed of inorganic substances such as semiconductors, glass, and ceramics, organic substances such as polyimide and polycarbonate, and composites such as glass / epoxy. The first circuit substrate 11 may be a plastic substrate. The first circuit component 13 may be, for example, a plastic substrate on which circuit electrodes are formed (a plastic substrate made of organic substances such as polyimide, polycarbonate, polyethylene terephthalate, and cycloolefin polymer), and the second circuit component 16 may be, for example, an IC chip such as a driver IC. The plastic substrate on which electrodes are formed may also be a substrate on which, for example, a pixel driving circuit such as an organic TFT or a plurality of organic EL elements R, G, and B are regularly arranged in a matrix to form a display area.
[0120] The first electrode 12 and the second electrode 15 may be electrodes containing metals such as gold, silver, tin, ruthenium, rhodium, palladium, osmium, iridium, platinum, copper, aluminum, molybdenum, titanium, and oxides such as indium tin oxide (ITO), indium zinc oxide (IZO), and indium gallium zinc oxide (IGZO). The first electrode 12 and the second electrode 15 may be electrodes formed by stacking two or more of these metals, oxides, and the like. The electrode formed by stacking two or more may have more than two layers or more than three layers. In the case where the first circuit component 13 is a plastic substrate, the first electrode 12 may be an electrode having a titanium layer on the outermost surface. The first electrode 12 and the second electrode 15 may be circuit electrodes or bump electrodes. At least one of the first electrode 12 and the second electrode 15 may be a bump electrode. In Figure 2 In the figure, the first electrode 12 is a circuit electrode and the second electrode 15 is a bump electrode.
[0121] The circuit connection portion 17 includes a cured product of the adhesive film 10. The circuit connection portion 17 can be made of the cured product of the adhesive film 10. The circuit connection portion 17 has, for example: a first cured product region 18, which is located on the first circuit component 13 side in the direction in which the first circuit component 13 and the second circuit component 16 are opposite to each other (hereinafter referred to as the "opposing direction"), and is made of a cured product of the (B) component and a cured product of the (C) component, etc., in the first adhesive layer except for the conductive particles 4; a second cured product region 19, which is located on the second circuit component 16 side in the opposite direction, and is made of a cured product of the (C) component, etc., in the second adhesive layer; and conductive particles 4, which are at least interposed between the first electrode 12 and the second electrode 15 to electrically connect the first electrode 12 and the second electrode 15 to each other. Figure 2As shown, the circuit connection portion 17 may not have two distinct regions between the first cured product region 18 and the second cured product region 19 , but may form one cured product region by mixing the cured product derived from the first adhesive layer and the cured product derived from the second adhesive layer.
[0122] Examples of circuit connection structures include: a flexible organic electroluminescent color display (organic EL display) formed by connecting a plastic substrate with organic EL elements regularly arranged thereon and a driving circuit element as a driver for image display, a touch panel formed by connecting a plastic substrate with organic EL elements regularly arranged thereon and a position input element such as a touch pad, etc. The circuit connection structure can be applied to various displays such as smartphones, tablet computers, televisions, car navigation systems, wearable terminals, furniture, home appliances, daily necessities, etc.
[0123] Figure 3 This is a schematic cross-sectional view showing one embodiment of a method for manufacturing a circuit-connected structure. Figure 3 (a) and Figure 3 (b) is a schematic cross-sectional view showing each process. Figure 3 As shown, the manufacturing method of the circuit connection structure 20 includes the following steps: the above-mentioned adhesive film 10 is placed between the first circuit component 13 having the first electrode 12 and the second circuit component 16 having the second electrode 15, and the first circuit component 13 and the second circuit component 16 are thermally pressed to electrically connect the first electrode 12 and the second electrode 15 to each other.
[0124] Specifically, if Figure 3 As shown in (a), first, prepare a first circuit component 13 including a first electrode 12 formed on a first circuit substrate 11 and a main surface 11a of the first circuit substrate 11, and a second circuit component 16 including a second electrode 15 formed on a second circuit substrate 14 and a main surface 14a of the second circuit substrate 14.
[0125] Next, the first circuit member 13 and the second circuit member 16 are arranged so that the first electrode 12 and the second electrode 15 face each other, and the adhesive film 10 is arranged between the first circuit member 13 and the second circuit member 16. Figure 3 As shown in (a), the adhesive film 10 is laminated on the first circuit member 13 so that the first adhesive layer 1 side is opposed to the main surface 11a of the first circuit substrate 11. Then, the second circuit member 16 is arranged on the first circuit member 13 laminated with the adhesive film 10 in such a manner that the first electrode 12 on the first circuit substrate 11 and the second electrode 15 on the second circuit substrate 14 are opposed to each other.
[0126] And, if Figure 3As shown in (b), the first circuit component 13, the adhesive film 10 and the second circuit component 16 are heated and pressed in the thickness direction, thereby thermally pressing the first circuit component 13 and the second circuit component 16 together. Figure 3 As shown by the arrow in (b), the second adhesive layer 2 has an uncured thermosetting component that can flow, and thus it is cured by the above-mentioned heating while flowing in a manner to fill the gaps between the second electrodes 15. As a result, the first electrode 12 and the second electrode 15 are electrically connected to each other via the conductive particles 4, and the first circuit component 13 and the second circuit component 16 are bonded to each other, so that Figure 2 The circuit connection structure 20 shown in FIG. In the manufacturing method of the circuit connection structure 20 of the present embodiment, since a part of the first adhesive layer 1 is a layer cured by light irradiation, the conductive particles 4 are fixed in the first adhesive layer 1, and the first adhesive layer 1 hardly flows during the above-mentioned thermocompression bonding, and the conductive particles are effectively captured between the opposing electrodes, thereby reducing the connection resistance between the opposing first electrode 12 and the second electrode 15. In addition, if the thickness of the first adhesive layer is 5 μm or less, it tends to be possible to further effectively capture the conductive particles during circuit connection.
[0127] The heating temperature during thermocompression bonding can be appropriately set, but for example, it can be 50 to 190°C. Regarding pressurization, there is no particular limitation as long as it is within the range that does not damage the adherend, but in the case of COP packaging, for example, the area conversion pressure on the bump electrode can be 0.1 to 50 MPa. And, in the case of COG packaging, for example, the area conversion pressure on the bump electrode can be 10 to 100 MPa. These heating and pressurization times can be in the range of 0.5 to 120 seconds.
[0128] Example
[0129] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0130] [Preparation of the First Adhesive Layer and the Second Adhesive Layer]
[0131] The following materials were used to prepare the first adhesive layer and the second adhesive layer.
[0132] (A) Ingredients: Conductive particles
[0133] Conductive particles A-1: Conductive particles with an average particle size of 3.2 μm were used. The surface of the plastic core was plated with Ni, and the outermost surface was subjected to displacement plating with Pd.
[0134] (B) Component: Photocurable resin component
[0135] (B1) Component: Radical polymerizable compound
[0136] Radical polymerizable compound B1-1: A-BPEF70T (ethoxylated fluorene di(meth)acrylate (bifunctional), manufactured by SHIN-NAKAMURA CHEMICAL CO, LTD.), diluted with toluene to a nonvolatile content of 70% by mass.
[0137] Radical polymerizable compound B1-2: VR-90 (bisphenol A type epoxy (meth) acrylate (bifunctional) (vinyl ester resin), manufactured by SHOWA DENKO KK)
[0138] Component (B2): Photoradical polymerization initiator
[0139] Photoradical polymerization initiator B2-1: Irgacure 907 (a compound having an α-aminoalkylphenone structure, manufactured by BASF Corporation)
[0140] (C) Component: Thermosetting resin component
[0141] (C1) Component: Cationic polymerizable compound
[0142] Cationic polymerizable compound C1-1: OXT-221 (3-ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane (oxetane compound), manufactured by TOAGOSEI CO., LTD.)
[0143] Cationic polymerizable compound C1-2: CEL2021P (3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate (alicyclic epoxy compound), manufactured by Daicel Corporation)
[0144] (C2) Component: Thermal cationic polymerization initiator
[0145] Thermal cationic polymerization initiator C2-1: CXC-1821 (N-(p-methoxybenzyl)-N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, manufactured by King Industries, Inc.)
[0146] (D) Ingredient: Thermoplastic resin
[0147] Thermoplastic resin D-1: FX293 (biphenyl, fluorene-type phenoxy resin, weight average molecular weight: 45,000, glass transition temperature: 158° C., manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), diluted with methyl ethyl ketone to a nonvolatile content of 40% by mass.
[0148] Thermoplastic resin D-2: ZX1356-2 (bisphenol A and bisphenol F copolymer phenoxy resin, weight average molecular weight: 70,000, glass transition temperature: 71°C, manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), diluted with methyl ethyl ketone to a non-volatile content of 50% by mass.
[0149] Thermoplastic resin D-3: YP-70 (bisphenol A type and bisphenol F type copolymerized phenoxy resin, weight average molecular weight: 55000, glass transition temperature: 70°C, manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), diluted with methyl ethyl ketone to a non-volatile content of 50% by mass.
[0150] Thermoplastic resin D-4: FX316 (bisphenol F type phenoxy resin, weight average molecular weight: 52000, glass transition temperature: 65°C, manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), diluted with methyl ethyl ketone to a non-volatile content of 40% by mass.
[0151] (E) Ingredient: Coupling agent
[0152] Coupling agent E-1: SH-6040 (3-glycidyloxypropyltrimethoxysilane, manufactured by Dow Corning Toray Co., Ltd.)
[0153] (F) Ingredients: Filling materials
[0154] Filler F-1: SE2050 (silicon dioxide fine particles, manufactured by ADMATECHS COMPANY LIMITED)
[0155] <Preparation of the first adhesive film (first adhesive layer)>
[0156] After obtaining a composition obtained by mixing the materials shown in Table 1 with the composition ratio shown in Table 1 (the numerical values in Table 1 refer to the amount of non-volatile components), the composition is applied while applying a magnetic field to a demolding-treated PET (polyethylene terephthalate) film, and the organic solvent is dried with hot air at 70°C for 5 minutes, thereby obtaining composition layers 1a and 1b containing the respective components. The composition layers 1a and 1b are applied so that the thickness after drying reaches the thickness of the first adhesive film (first adhesive layer) 1A and 1B described in Tables 3 and 4, respectively. With respect to the composition layer 1a, the layer is irradiated with light (UV irradiation: metal halide lamp, cumulative light intensity: 1900 to 2300 mJ / cm 2 ), thereby obtaining the first adhesive film 1A. The composition layer 1b was used as the first adhesive film 1B without being irradiated with light.
[0157] [Table 1]
[0158]
[0159] <Preparation of the second adhesive film (second adhesive layer)>
[0160] After mixing the materials shown in Table 2 at the composition ratio shown in Table 2 (the values in Table 2 refer to the amount of non-volatile components), the materials were applied on a PET (polyethylene terephthalate) film subjected to a mold release treatment, and the organic solvent was dried, thereby obtaining the second adhesive films 2A to 2G containing the respective components. The second adhesive films 2A to 2F were applied to a thickness of 10 to 12 μm after drying, and the second adhesive film 2G was applied to a thickness of 8 to 10 μm after drying.
[0161] [Table 2]
[0162]
[0163] (Examples 1 to 4 and Comparative Examples 1 to 3)
[0164] [Manufacturing of adhesive film]
[0165] The adhesive films having the structures shown in Table 3 were prepared using the first adhesive film and the second adhesive film prepared as described above. For example, in the adhesive film of Example 1, the first adhesive film 1A was bonded to the second adhesive film 2A while applying a temperature of 50 to 60° C. to obtain the adhesive film of Example 1. As for the adhesive films of Examples 2 to 4 and Comparative Examples 1 to 3, adhesive films having the structures shown in Tables 3 and 4 were prepared in the same manner as in Example 1.
[0166] [Measurement of minimum melt viscosity]
[0167] The minimum melt viscosity of the adhesive films of Examples 1 to 4 and Comparative Examples 1 to 3 was measured. The adhesive films were laminated using a laminator so that the thickness was 500 μm or more to obtain a laminate. The release-treated PET was peeled off from the obtained laminate and cut into 10.0 mm × 10.0 mm pieces to obtain a measurement sample. The minimum melt viscosity of the obtained measurement sample (trade name: ARES-G2, manufactured by TA Instruments, heating rate: 10°C / min) was measured using a viscoelasticity measuring device. The results are shown in Tables 3 and 4.
[0168] [Measurement of Thickness of First Adhesive Layer in Adhesive Film]
[0169] The thickness of the first adhesive layer was measured for the adhesive films of Examples 1 to 4 and Comparative Examples 1 to 2. In the measurement, the adhesive film was sandwiched between two glasses (thickness: about 1 mm), and a resin composition composed of 100 g of bisphenol A epoxy resin (trade name: JER811, manufactured by Mitsubishi Chemical Corporation) and 10 g of a curing agent (trade name: Epomount curing agent, manufactured by Refine Tec Ltd.) was cast, and then the cross section was ground using a grinder, and the thickness of the first adhesive layer was measured using a scanning electron microscope (SEM, trade name: SE-8020, manufactured by Hitachi High-Tech Science Corporation). The results are shown in Tables 3 and 4.
[0170] [Evaluation of Circuit Connection Structure]
[0171] (Preparation of circuit components)
[0172] As the first circuit component, a circuit component having a plastic substrate (thickness: 0.05 mm) with a Ti / Al / Ti circuit, PSA (thickness: 15 μm) and PET (thickness: 38 μm) bonded to the lower surface of the plastic substrate was prepared. As the second circuit component, an IC chip with gold bumps (0.9 mm × 20.3 mm, thickness: 0.3 mm, size of bump electrodes: 12 μm × 100 μm, space between bump electrodes: 24 μm, bump electrode thickness: 12 μm) was prepared.
[0173] (Fabrication of Circuit Connection Structure)
[0174] Circuit connection structures were fabricated using the adhesive films of Examples 1 to 4 and Comparative Examples 1 to 3. The adhesive films were cut into 2.0 mm widths and placed on the first circuit component so that the first adhesive layer was in contact with the first circuit component. A thermal temporary pressure bonding device (LD-06, manufactured by OHASHI ENGINEERING Co., Ltd.) consisting of a carrier including a ceramic heater and a tool (8 mm × 50 mm) was used at 70°C and 0.98 MPa (10 kgf / cm 2 ) for 2 seconds to attach the adhesive film to the first circuit component, and peel off the release film on the side of the adhesive film opposite to the first circuit component. Next, after the bump electrode of the first circuit component and the circuit electrode of the second circuit component are aligned, a heating tool of 8 mm × 45 mm is used, and Teflon (registered trademark) with a thickness of 50 μm is used as a buffer material, and heating and pressurizing are performed for 5 seconds under the conditions of connection conditions of 170° C. and area conversion pressure of 30 MPa on the bump electrode, and the second adhesive layer of the adhesive film is attached to the second circuit component, thereby producing a circuit connection structure.
[0175] (Evaluation of deformation amount of plastic substrate)
[0176] For the produced circuit connection structure, the distance between the output bump and the input bump of the IC chip on the plastic substrate was measured from the surface of the plastic substrate using a three-dimensional shape measuring device (trade name: LT-9010M, manufactured by FASYSTEMS.), and the difference between the maximum and minimum values of the distance was taken as the deformation amount of the plastic substrate. The results are shown in Tables 3 and 4.
[0177] (Observation of circuit wiring on plastic substrate)
[0178] The produced circuit connection structure was observed from the surface of the plastic substrate using a differential interference contrast microscope (trade name: L300ND, manufactured by NIKON CORPORATION) to evaluate the state of the wiring (whether or not there was disconnection).
[0179] (Evaluation of connection resistance)
[0180] For the produced circuit connection structure, the initial connection resistance (on-resistance) and the connection resistance (on-resistance) after storage for 500 hours under the conditions of temperature 85°C and humidity 85%RH were measured by the four-terminal test method. In the measurement, a constant current power supply device R-6145 manufactured by ADVANTEST CORPORATION was used to apply a constant current (1mA) between the circuit electrode of the first circuit component of the circuit connection structure and the circuit electrode of the second circuit component (connection portion). The potential difference of the connection portion when the current was applied was measured using a digital multimeter (R-6557) manufactured by ADVANTEST CORPORATION. The potential difference was measured at any 14 points and its average value was calculated. The average value of the potential difference was converted into a connection resistance value, and the difference between the initial connection resistance value and the connection resistance value after storage for 500 hours under the conditions of temperature 85°C and humidity 85%RH was evaluated according to the following benchmark. The results are shown in Tables 3 and 4. In this evaluation, it can be said that the smaller the difference in connection resistance value is, the better the conduction characteristics between the opposing electrodes can be ensured.
[0181] A: less than 2Ω
[0182] B: 2Ω or more and less than 3Ω
[0183] C: 3Ω or more
[0184] (Evaluation of Conductive Particle Capturing Performance)
[0185] In addition to using a glass substrate with Al (thickness: 0.5mm) as the first circuit component, a circuit connection structure was made in the same manner as described above. Using a differential interference contrast microscope (trade name: L300ND, manufactured by NIKONCORPORATION.), the circuit connection structure made was observed from a glass substrate with Al, the number of conductive particles present in each gold bump was measured, and the average value was calculated. For one circuit connection structure, the measurement object of the number of conductive particles present on the gold bump was set to 100, the average value of the 100 was set to the number of conductive particle captures, and evaluated according to the following benchmarks. The results are shown in Tables 3 and 4. In this evaluation, it can be said that the larger the number of conductive particle captures, the better the good conduction characteristics between the opposing electrodes can be ensured.
[0186] A: More than 15
[0187] B: 10 or more and less than 15
[0188] C: Less than 10
[0189] [Table 3]
[0190] Example 1 Example 2 Example 3 Example 4 First adhesive layer 1A 1A 1A 1A Thickness of the first adhesive layer (μm) 1.8 1.8 1.8 1.8 Second adhesive layer 2A 2B 2C 2D Minimum melt viscosity (Pa·s) 500 800 1000 1500 Deformation of substrate (μm) 7.0 6.3 5.8 5.0 Whether there is disconnection none none none none Connecting resistor A A A B Conductive particle capture B A A A
[0191] [Table 4]
[0192] Comparative Example 1 Comparative Example 2 Comparative Example 3 First adhesive layer 1A 1A 1B Thickness of the first adhesive layer (μm) 1.8 1.8 6 Second adhesive layer 2E 2F 2G Minimum melt viscosity (Pa·s) 400 1800 800 Deformation of substrate (μm) 7.5 4.2 6.5 Whether there is disconnection have none none Connecting resistor A C A Conductive particle capture B A C
[0193] As shown in Table 3, the adhesive films of Examples 1 to 4 are excellent in all items. On the other hand, the adhesive film of Comparative Example 3, which does not have the specified first adhesive layer, is insufficient in terms of conductive particle capture. Moreover, in the adhesive film of Comparative Example 1 having a minimum melt viscosity of less than 450 Pa·s, the deformation of the substrate is large and disconnection is observed. In addition, the adhesive film of Comparative Example 2 having a minimum melt viscosity of more than 1600 Pa·s is insufficient in terms of connection resistance. From these results, it is confirmed that the adhesive film of the present invention can suppress circuit disconnection during thermocompression bonding and can ensure good conduction characteristics between opposing electrodes of the circuit connection structure.
[0194] Explanation of symbols
[0195] 1-first adhesive layer, 2-second adhesive layer, 4-conductive particles, 5-adhesive component, 10-adhesive film for circuit connection (adhesive film), 11-first circuit substrate, 12-first electrode (circuit electrode), 13-first circuit component, 14-second circuit substrate, 15-second electrode (bump electrode), 16-second circuit component, 17-circuit connecting portion, 20-circuit connecting structure.
Claims
1. An adhesive film for circuit connection, comprising: a first adhesive layer comprising conductive particles, a cured product of a photocurable resin component, and a first thermosetting resin component; and a second adhesive layer disposed on the first adhesive layer and containing a second thermosetting resin component, The first thermosetting resin component and the second thermosetting resin component include a cationically polymerizable compound and a thermal cationic polymerization initiator. The photocurable resin component includes a free radical polymerizable compound. The minimum melt viscosity is 450~1600Pa·s.
2. The circuit connection adhesive film according to claim 1, wherein: The cationically polymerizable compound is at least one selected from the group consisting of oxetane compounds and alicyclic epoxy compounds.
3. The circuit connection adhesive film according to claim 1 or 2, wherein: The thermal cationic polymerization initiator is a salt compound having an anion containing boron as a constituent element.
4. The circuit connection adhesive film according to claim 1 or 2, wherein: The first adhesive layer has a thickness of 5 μm or less.
5. A method for manufacturing a circuit connection structure, comprising the following steps: The circuit connection adhesive film according to any one of claims 1 to 4 is interposed between a first circuit component having a first electrode and a second circuit component having a second electrode, and the first circuit component and the second circuit component are thermally pressed to electrically connect the first electrode and the second electrode to each other.
6. A circuit connection structure, comprising: a first circuit component having a first electrode; a second circuit component having a second electrode; and a circuit connection portion, disposed between the first circuit component and the second circuit component, and electrically connecting the first electrode and the second electrode to each other; The circuit connection portion includes a cured product of the circuit-connecting adhesive film according to any one of claims 1 to 4.
Citation Information
Patent Citations
Connection body, manufacturing method therefor, electronic component connection method and electronic component
JP2016054288A
Insulation material, laminate, connection structure and manufacturing method of laminate and connection structure
JP2013058412A
Anisotropic conductive film and method for producing same
WO2014021457A1
Anisotropic electroconductive adhesive and production method for connection body
WO2018180685A1